Fenomena Belief Dilema dan Miskonsepsi Pengikut Buddha dalam Menjalankan Atthasila Saat Sebulan Pendalaman Dhamma - Bumi Horas (Universitas Hamzanwadi, 2025)
This research was motivated by the decreasing interest of Buddhists at the Sasanadipa Vihara to practice Atthasila during the Month of Dhamma Study leading up to Vesak. The purpose of this study was to analyze the existence of belief dilemma and misconception among followers of the Sasanadipa Makassar Buddhist Temple in carrying out Atthasila, the differences in factors that contribute to belief dilemma and misconception in three age groups of Buddhist followers, what factors can arouse the interest of a small number of followers of the Sasanadipa Makassar Buddhist Temple to practice Atthasila, and what factors trigger most Buddhist followers not to want to practice Atthasila. The implications of this study also explain the methods used to overcome the belief dilemma and misconception of followers of the Sasanadipa Makassar Buddhist Temple in carrying out Atthasila. Researchers use a qualitative descriptive approach, specifically analytical descriptive. The choice of this approach was to obtain a description of